The development of numeracy problems using light rail transit context - Yessi Permata Sari; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Jurnal Elemen, 2023)
The emergence of this research is due to the low numeracy skills of students in Indonesia. It is due to the soft critical thinking skills of students. One of the strategies that can be done is to develop PISA-type questions and activities. This study aims to produce PISA-type questions and activities using a valid and practical context using Light Rail Transit. This research is a design research type of development research which consists of a preliminary evaluation stage and a formative evaluation stage. This study involved students of eighth-grade junior high school students in Palembang City, totaling 34 students with various skills. The analysis of the results of this study was qualitatively based on data from the field received in the form of interviews, document reviews, observations, and tests to see student activities in solving questions and activities. The result of this research is the development of PISA-type questions and activities, namely four student activities and six evaluation questions using the Light Rail Transit context. In conclusion, PISA-type questions and activities in the context of Light Rail Transit can be used in classroom learning to improve students' numeracy skills.